Mindfulness for Addiction Recovery: A Cognitive Disciplinary Preventive Approach to Avoid Relapse into Substance Abuse - Swarna Weerasinghe ,; Shaun Bartone, (Journal of Basic & Applied Sciences, 2016)
The present paper is based on a literature review and a pilot study that observed a small group of participants in a bi-weekly substance abuse treatment program that employs mindfulness training to help subjects avoid relapse into substance abuse. “Mindfulness” is defined as a state of non-judgemental self-awareness. The program that we propose combines three treatment modalities: 1) yoga practice, 2) silent meditation practice, and 3) self-reflection, a peer-led discussion on issues affecting recovery from substance abuse. Discussion of issues affecting substance abuse employs “cognitive disciplines” derived from the 12 Steps of Alcoholics Anonymous and Buddhist teachings on “mindfulness” and “relief from suffering”. The pilot study examines the effect of combining stress reduction and mindfulness of the body, induced by yoga practice; mindfulness of mental processes, aided by silent meditation, and self-awareness of one’s emotional and behavioural responses to stress, learned using the “cognitive disciplines”. This multi-disciplinary process is applied to influence one’s experience of stress and addictive patterns of behaviour. The present case study examines whether the combination of the three treatment modalities improves the participants’ ability to avoid relapse into substance abuse. This study follows an approach similar to the one used by Bryan and Zipp (2014) in their research involving the effects of mindfulness meditation during yoga and cycling from a physical-behavioural perspective and Groves’ (2014) approach to mental wellness. Our preliminary findings of the participants’ observations resulting from the pilot study and our literature review were combined into a theoretical framework which is comprised of a Three Pronged Cognitive Behavioral Therapy (TPCBT) for addiction recovery.